Mass tourism and overtourism in Polish agglomerations. Poznan and Wroclaw case studies - Komorowski, Józef; Hołderna-Mielcarek, Bernadeta (Turystyka masowa i overtourism w polskich aglomeracjach na przykładzie Poznania i Wrocławia, 2019)
The goal of this paper was to identify the functions of mass tourism and overtourism and explore the possibilities of the optimisation of solutions allowing to prevent excessive levels of tourism, using the example of two Polish agglomerations, Poznan and Wroclaw. Based on theoretical solutions and proposals for actions in selected European cities, research was carried out among local experts on tourism. The results provide an example of local perception of the analysed problem. The conclusions indicate that in these cities the problem of mass tourism and especially overtourism does not exist; and that tourism is perceived through the lens of economic effects, which are seen as a very significant positive attribute. The optimization of mass tourism solutions that support limiting excessive tourism includes e.g: the distribution of tourist infrastructure and attractions in various parts of the city, creating tourist products covering urban space as well as suburban areas, cooperation and coordination in the field of tourist initiatives
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 68-78
Keywords: mass tourism; overtourism; optimization of mass tourism solutions; turystyka masowa; optymalizacja rozwiązań w turystyce masowej